A Study of Young Adults’ Intention towards Genetically Modified Foods: Mediating Effect of Health Belief (Indian Journal of Public Health Research & Development, 2020)
Thestudy is an attempt to gauge intentions of Indian young adults towards purchase of GM food in threestates of north India with 528 respondents as sample. The study employed questionnaire method of datacollection using Likert scale. Structural Equation Modeling through AMOS is used for data analysis. Resultsreveal that information about GM foods, their effects, safety issues and health beliefs of young adults aresignificant determinants of GM food purchase intention. There is an insignificant relationship betweenemotional involvement and purchase intentions. Health belief mediates between the variables. Results canaugment the current understanding of governments, organizations and other bodies towards the behavior ofyoung adults towards GM foods.
Keywords: Adoption, Consumers, Emotional-Involvement, Health Belief, Intention